Rhythmic auditory cues improve gait asymmetry during unobstructed walking in people with Parkinson’s disease but have no effect on obstacle avoidance - AsymmGait-Parkinson study - Cursiol, Jônatas Augusto; dos Santos, Paulo Cezar Rocha; Beretta, Victor Spiandor; Orcioli-Silva, Diego; Simieli, Lucas; Schlenstedt, Christian; Coelho, Daniel Boari; Barbieri, Fabio Augusto (Frontiers in Aging Neuroscience, 2025)
IntroductionThis study investigated the influence of rhythmic auditory cues (RAC) on gait asymmetry (GA) during unobstructed and obstacle avoidance walking in people with Parkinson’s disease (PD) and neurologically healthy individuals.MethodsThirteen individuals with PD (70.33 ± 6.02 years) and 13 healthy controls (CG) (70.77 ± 7.56 years) participated in this study. They performed a total of five trials during unobstructed walking and 10 trials during obstacle walking under each auditory cue condition (without and with RAC). For obstacle walking, five trials were performed with each limb as leading during obstacle avoidance. First, the volunteers performed the trials without RAC. The trial order, unobstructed or obstacle walking, was randomly defined, and the cues (controlled by a metronome) were personalized according to participants’ cadence. The symmetric index of gait parameters was analyzed using 2 × 2 factorial analysis of variance (group and RAC as factors) separately for each gait type (unobstructed and obstructed walking).ResultsA group-by-auditory cue interaction for step velocity (p = 0.027) showed that the PD group exhibited 57.6% reduced asymmetry with RAC during unobstructed walking, with no significant effects observed for the CG. However, RAC had no effect on GA during obstacle avoidance walking in people with PD. Conversely, the CG exhibited 10.5% greater step length asymmetry, 7.1% greater step duration asymmetry, 7.0% greater step velocity asymmetry, and 10.6% greater double support duration asymmetry during obstacle avoidance with RAC (p < 0.001).ConclusionWe conclude that RAC can reduce GA in people with PD during unobstructed walking, but appear to have no effect and negative effects on GA during obstacle walking in people with PD and neurologically healthy individuals, respectively.